Pseudoplatystoma metaense and P. orinocoense (Siluriformes: Pimelodidae) from the Orinoco basin, Venezuela: cytogenetic and molecular analyses - Nirchio, M.; Mujica, A.; Oliveira, C. [UNESP]; Granado, A.; Mora, J.; Hett, A. K.; Rossi, A. R.; Milana, V.; Sola, L. (Taylor & Francis Ltd, 2013)
The genus Pseudoplatystoma includes catfish species distributed throughout the fresh waters of South America. These species are important fisheries resources and play a significant ecological role due to their piscivorous and migratory habits. The taxonomy of this genus is still debated: traditionally, only three species have been recognised, but recently, this number was raised to eight. The validity of these eight morphospecies, however, was not confirmed by two subsequent molecular phylogenetic studies, which identified either five or four main clades. In this study, we focused on the two morphospecies restricted to the Orinoco basin, P. metaense and P. orinocoense, which have been assigned to either the same or different clades in previous studies. We carried out cytogenetic analyses to describe their unknown karyotypes and to look for cytotaxonomic markers. We also analysed their mitochondrial sequences in order to assign the sampled specimens to the previously identified molecular clades. The two presumptive species show similar karyotypes (2n=56, 42 biarmed and 14 uniarmed chromosomes) and cytogenetic features in terms of the constitutive heterochromatin distribution and the number and location of minor and major ribosomal genes. Thus, no species-specific chromosome markers could be identified. The analysis of cytochrome b and cytochrome oxidase I mitochondrial genes (carried out by retrieving all the mtDNA Pseudoplatystoma sequences available in GenBank) distributed the sampled specimens into two distinct molecular clades and confirmed the need to re-evaluate, by parallel morphological and molecular analyses, the monophyly of some lineages.
Keywords: COI; cyt b; FISH; karyotype; ribosomal genes